Assessment of Environmental Attitude of Adolescent of Bikaner City. (2nd January 2017) - Chouhan, Sunita; Bhatnagar, Bharti; Suman,; Kaur, Manpreet
ABSTRACT: Environmental attitudes are important because they often, but not always, determine behavior that either increases or decreases environmental quality. Environmental education aims to improve environmental attitudes but has mixed results. Environmental attitudes might be better described as having preservation and utilization dimensions. The canvas of environmental education includes main integrated components awareness and conservation. Hence the present study was undertaken to assess the environmental attitude of adolescents studying in senior secondary schools of Bikaner city. The total sample for the present study was 120 randomly selected adolescents. Data was collected through the Standardized Environmental Attitude Scale developed. To assess the areas of environmental attitude of the selected respondents, frequency and percentage were computed. The major findings revealed that none of the boys and girls were found to have low level of attitude. It can be concluded that although the adolescents had awareness and favorable attitude about different areas of environmental attitude. It was not sufficient and there was a need for imparting quality knowledge to the adolescents through appropriate environmental education program.